Seismic performance enhancement of three-dimensional frame structures via inerter-based control systems - Di Egidio, Angelo; Contento, Alessandro (Frontiers in Built Environment, 2025)
Improving the seismic response of new and existing structures is a fundamental topic in civil engineering. Often, in structural mechanics this issue is addressed through low-dimensional mechanical models capable of capturing the primary dynamics of the structure. In contrast to most studies in the scientific literature that use two-dimensional models to describe structural behavior, this paper employs a low-dimensional, three-dimensional (3D) mechanical model to capture the seismic response of a structure, also accounting for its torsional effects. This low-dimensional model is used to investigate two different methods for improving seismic response. One approach involves inerter devices directly connected to the structure, while the other is based on connecting the structure to external auxiliary structures, equipped in turn with inerters. Therefore, in this case, the inerter devices are connected directly to the external structures. The responses of the original stand-alone frame structure and those with the two proposed methods are compared to assess the effectiveness of each approach. Three different earthquake records are used as base excitation. The results are presented in performance curves and maps, showing the response in terms of displacements of key points of the structure as various system parameters are varied. The results reveal the good performance of both methods over a wide range of parameters, with particularly favorable results for the approach using external structures equipped with inerter devices.